\(A=\sqrt{32.200}\)

b)\(B=\sqrt{5}...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 7 2021

\(A=\sqrt{32.200}=\sqrt{32}\sqrt{200}=4\sqrt{2}.\sqrt{2}\sqrt{100}\)

\(A=4.2.10=80\)

\(B=\sqrt{5}.\sqrt{125}=\sqrt{5}.5\sqrt{5}=5.5=25\)

21 tháng 7 2019

a)\(2\sqrt{5}-\sqrt{125}-\sqrt{80}+\sqrt{605}\)

\(2\sqrt{5}-5\sqrt{5}-4\sqrt{5}+11\sqrt{5}\)

\(4\sqrt{5}\)

b) \(\sqrt{15-\sqrt{216}}+\sqrt{33-12\sqrt{6}}\)

\(\sqrt{3\left(5-2\sqrt{6}\right)}-\sqrt{33-12\sqrt{6}}\)

\(\sqrt{3\left(5-2\sqrt{6}\right)}-\sqrt{3\left(11-4\sqrt{6}\right)}\)

21 tháng 7 2019

\(a,2\sqrt{5}-\sqrt{125}-\sqrt{80}+\sqrt{605}\)

\(=2\sqrt{5}-\sqrt{5^2.5}-\sqrt{4^2.5}+\sqrt{11^2.5}\)

\(=2\sqrt{5}-5\sqrt{5}-4\sqrt{5}+11\sqrt{5}\)

\(=4\sqrt{5}\)

\(b,\sqrt{15-\sqrt{216}}+\sqrt{33-12\sqrt{6}}\)

\(=\sqrt{15-6\sqrt{6}}+\sqrt{33-12\sqrt{6}}\)

\(=\sqrt{\left(3-\sqrt{6}\right)^2}+\sqrt{\left(3-2\sqrt{6}\right)^2}\)

\(=|3-\sqrt{6}|+|3-2\sqrt{6}|\)

\(=3-\sqrt{6}+2\sqrt{6}-3\)

\(=\sqrt{6}\)

30 tháng 6 2019

a)\(=\sqrt{\frac{5.5^2}{3^5.2^6}}=\sqrt{\frac{5}{3^5}}.\frac{5}{2^3}=\frac{5\sqrt{5.3^5}}{3^5.2^3}\)

b)\(=\left(3\sqrt{5}-2\sqrt{5}+\sqrt{5}\right):\sqrt{6}\)

\(=\frac{2\sqrt{5}}{\sqrt{6}}\)\(=\frac{\sqrt{30}}{3}\)

Câu c ttự

d)\(=\sqrt{2^8.5^2}=2^4.5=80\)

e)\(=\sqrt{\left(\frac{3}{4}\right)^2:\left(\frac{5}{6}\right)^2}=\frac{9}{10}\)

30 tháng 6 2019

Mình cảm ơn ạ

\(a,\sqrt{\frac{72}{9}}:\sqrt{8}=\frac{\sqrt{72}}{\sqrt{9}}.\frac{1}{\sqrt{8}}\)

\(=\frac{6\sqrt{2}}{3}.\frac{1}{2\sqrt{2}}\)

\(=1\)

\(b,\left(7\sqrt{48}+3\sqrt{27}-2\sqrt{12}\right):\sqrt{3}=\left(28\sqrt{3}+9\sqrt{3}-4\sqrt{3}\right):\sqrt{3}\)

\(=33\sqrt{3}:\sqrt{3}\)

\(=33\)

\(c,\left(\sqrt{125}+\sqrt{245}-\sqrt{5}\right):\sqrt{5}=\left(5\sqrt{5}+7\sqrt{5}-\sqrt{5}\right):\sqrt{5}\)

\(=11\sqrt{5}:\sqrt{5}\)

\(=11\)

\(d,\left(\sqrt{\frac{1}{7}}-\sqrt{\frac{16}{7}}+\sqrt{7}\right):\sqrt{7}=\left(\frac{1}{\sqrt{7}}-\frac{4}{\sqrt{7}}+\frac{7}{\sqrt{7}}\right):\sqrt{7}\)

\(=\frac{4}{\sqrt{7}}.\frac{1}{\sqrt{7}}=\frac{4}{7}\)

18 tháng 10 2020

a) \(\sqrt{36}.\sqrt{121}+\sqrt[3]{-64}-\sqrt[3]{125}\)

\(=6.11+\left(-4\right)-5=66-9=57\)

b) \(\sqrt{75}+\sqrt{\left(\sqrt{3}-2\right)^2}-30\sqrt{\frac{3}{25}}\)

\(=\sqrt{25.3}+\left|\sqrt{3}-2\right|-30.\frac{\sqrt{3}}{\sqrt{25}}\)

\(=5\sqrt{3}+2-\sqrt{3}-30.\frac{\sqrt{3}}{5}\)

\(=5\sqrt{3}+2-\sqrt{3}-6\sqrt{3}=2-2\sqrt{3}\)

c) \(\sqrt{11-4\sqrt{7}}-\frac{12}{1+\sqrt{7}}=\sqrt{7-4\sqrt{7}+4}-\frac{12}{1+\sqrt{7}}\)

\(=\sqrt{\left(\sqrt{7}-2\right)^2}-\frac{12}{1+\sqrt{7}}=\left|\sqrt{7}-2\right|-\frac{12}{1+\sqrt{7}}\)

\(=\left(\sqrt{7}-2\right)-\frac{12}{\sqrt{7}+1}=\frac{\left(\sqrt{7}-2\right)\left(\sqrt{7}+1\right)}{\sqrt{7}+1}-\frac{12}{\sqrt{7}+1}\)

\(=\frac{5-\sqrt{7}}{\sqrt{7}+1}-\frac{12}{\sqrt{7}+1}=\frac{-7-\sqrt{7}}{\sqrt{7}+1}\)

\(=\frac{-\sqrt{7}\left(\sqrt{7}+1\right)}{\sqrt{7}+1}=-\sqrt{7}\)

18 tháng 8 2016

a/ Đề sai

b/ \(\sqrt{125}-4\sqrt{45}+3\sqrt{2}-\sqrt{80}=5\sqrt{5}-12\sqrt{5}+3\sqrt{2}-4\sqrt{5}\)

\(=-11\sqrt{5}+3\sqrt{2}\)

c/ \(2\sqrt{\frac{27}{4}}-\sqrt{\frac{48}{9}}-\frac{2}{5}\sqrt{\frac{75}{16}}=2.\frac{3\sqrt{3}}{2}-\frac{4\sqrt{3}}{3}-\frac{2}{5}.\frac{5\sqrt{3}}{4}\)

\(=3\sqrt{3}-\frac{4\sqrt{3}}{3}-\frac{\sqrt{3}}{2}=\sqrt{3}\left(3-\frac{4}{3}-\frac{1}{2}\right)=\frac{7\sqrt{3}}{6}\)

d/ \(\left(\sqrt{99}-\sqrt{18}-\sqrt{11}\right)\cdot\sqrt{11}+3\sqrt{22}=33-3\sqrt{22}-11+3\sqrt{22}=22\)

 

6 tháng 8 2019

a, A= \(\frac{\sqrt{48-12\sqrt{7}}}{2}-\frac{\sqrt{48+12\sqrt{7}}}{2}\)

       = \(\frac{\sqrt{\left(\sqrt{42}-\sqrt{6}\right)^2}}{2}-\frac{\sqrt{\left(\sqrt{42}+\sqrt{6}\right)^2}}{2}\)

       = \(\frac{-2\sqrt{6}}{2}\)

       = \(-\sqrt{6}\)

29 tháng 7 2018

a)  \(\frac{\sqrt{2+\sqrt{3}}}{\sqrt{2}}=\frac{\sqrt{4+2\sqrt{3}}}{2}=\frac{\sqrt{\left(\sqrt{3}+1\right)^2}}{2}=\frac{\sqrt{3}+1}{2}\)

b)   \(\frac{\sqrt{6-2\sqrt{5}}}{1-\sqrt{5}}=\frac{\sqrt{\left(\sqrt{5}-1\right)^2}}{1-\sqrt{5}}=\frac{\sqrt{5}-1}{1-\sqrt{5}}=-1\)

p/s: chúc bạn học tốt

29 tháng 7 2018

a) \(\frac{\sqrt{2+\sqrt{3}}}{\sqrt{2}}=\frac{\sqrt{4+2\sqrt{3}}}{2}=\frac{\sqrt{3+2\sqrt{3}+1}}{2}=\frac{\sqrt{\left(\sqrt{3}+1\right)^2}}{2}=\frac{\sqrt{3}+1}{2}\)

b) \(\frac{\sqrt{6-2\sqrt{5}}}{1-\sqrt{5}}=\frac{\sqrt{5-2\sqrt{5}+1}}{1-\sqrt{5}}=\frac{\sqrt{\left(\sqrt{5}-1\right)^2}}{1-\sqrt{5}}=\frac{\sqrt{5}-1}{1-\sqrt{5}}=-1\)